Decision confidence: EEG correlates of confidence in different phases of an old/new recognition task. Issue 4 (2nd October 2019) - Krumpe, Tanja; Gerjets, Peter; Rosenstiel, Wolfgang; Spüler, Martin
ABSTRACT: We use an old-new recognition memory task to investigate the correlates of high and low decision confidence throughout all stages of the memory process. Group-level ERP analysis and single-trial and single-subject classification are performed on four stages of the task (information encoding, retrieval, old/new decision formation, and evaluative feedback processing). The study shows that decision confidence is significantly reflected on a group, as well as on a single-trial basis, in all investigated stages at the neural level, except during encoding. The most pronounced differences between high and low confidence can be found in the ERPs during feedback presentation after a correct answer, whereas almost no differences can be found following a wrong answers. In the feedback stage, the two levels of confidence can be separated with classification accuracies of up to 70 % on average, therefore showing potential to be used as a control state in a BCI application.